PELAKSANAAN TUGAS DAN WEWENANG DINAS PARIWISATA DAN KEBUDAYAAN KABUPATEN KUNINGAN DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH (PAD) - Ahmad Noor Kholis Majid , Indarja, Ratna Herawati (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2013)
Regional autonomy is defined as the effort to empower regions and the people to improve the people’s welfare in all life aspects including in tourism field. Therefore, tourism sector become one of regional potencies developed by all regional governments, particularly Kuningan District, to support the development of people’s welfare through increasing Regional Original Revenue (PAD). Regional Original Revenue (PAD) is the source of regional income obtained from its own region collected based on regional regulation in accordance with the applicable law (Article 1 of the Act No. 33, 2004). Then, Regional Original Revenue is the original source of original income coming from regional potencies. Regional Government can explore the sources of Regional Original Revenue optimally.The method applied in this research was normative juridical research meaning that anything written in laws or regulations is made into a concept as principle/ norm, and used as the standard for appropriate human behavior. The aim of this research is to recognize whether the implementation of duties and authorities of the Tourism and Culture Agency of Kuningan District, West Java, has been in accordance with the law or not.The research results show that the implementation of duties and authorities of the Tourism and Culture Agency of Kuningan District, West Java, has been regulated in the Regulation of Kuningan Regent No. 42, 2008 on the Main Duties, Functions, and Job Description of the Tourism and Culture Agency of Kuningan District from the side of product and attraction, facilities and infrastructure, market and promotion, and human resources. To find out the problems, several efforts have been performed by the Tourism and Culture Agency of Kuningan District by applying the Regional Regulation No. 7, 2009 on the Master Plan of Regional Tourism Development (RIPPDA). RIPPDA is the formulation of the major policies on the planning and using of tourism development in the region including the aspects of spatial planning, tourism business, supporting factors, and continuous tourism development with environmental conception for optimizing tourism potencies in harmony, balance, integrated, well-arranged, and preserved.